O romance africano e os posicionamentos das vozes femininas em Nervous Conditions de Tsitsi Dangarembga - Soares, Cláudia Regina (2016)
Nervous conditions (1988) by Zimbabwean Tsitsi Dangarembga is considered the first novel written in English by a black woman in Zimbabwe. The book soon became an icon in African postcolonial literature and a milestone in women's writing, depicting the struggles of African women in search of spaces to be heard in society and freed from patriarchal domination. The setting of the novel is pre-independent Zimbabwe, and the story takes place within a shona family context, an environment in which socialization of gender roles happens, particularly those related to women. The story is told by the main character, Tambu, who in a process of growth and maturation, also tells the story of four other women in her family and their men. Through the positioning of these female characters' voices, it is possible to notice how African women undergo from an early age experiences of being told to develop adequate feminine traits in their social environment, being consequently oppressed and silenced by male voices and tradition. The reading of Dangarembga's novel was the starting point for the investigation of women's situation in Zimbabwean society and African literature undergone in this paper, which proved African women's literary achievements were often ignored or neglected by international and African criticism. The main aim of this research is outlined then in two directions: to show the positionings of female voices in the bigger picture of African postcolonial literature, revealing the deletion attacks they suffered, but also their resistance and emergencies, and to analyze gender relationships through the themes and strategies employed by Dangarembga in Nervous conditions.